The Influence of Work Ethic, Leadership, And Job Satisfaction on The Performance of Grab Employees in The Surabaya Region - Ismawati*, Yesika; Kustiningsih, Nanik; Rahayu, Sri (Universitas Syiah Kuala, 2024)
Human resources are the most important part of the company's existence and sustainable development. However, researchers discovered the fact that the era of digitalization has become very dominant, and has had an impact on the role of humans being replaced by robots. However, the role of humans in transportation service companies such as Grab in Surabaya has proven to be irreplaceable. This research focuses on measuring the influence of work ethic, leadership, and job satisfaction on employee performance. This research revealed the fact that these three components are interrelated and are a focus that the company should understand. This research will focus on the measurement and impact of the three components on the company's overall performance.